Difficult caesarean section: A literature review. (March 2020) - Visconti, Federica; Quaresima, Paola; Rania, Erika; Palumbo, Anna Rita; Micieli, Mariella; Zullo, Fulvio; Venturella, Roberta; Di Carlo, Costantino
Abstract: Background: Caesarean section (CS) is usually perceived as a simple and safe alternative to natural birth, but in some instances can be technically difficult with consequent health hazards for both the mother and the fetus. We have proposed an evidence-based literature review of the most common difficult CS scenarios, with the aim to provide useful information about their management, possible prevention and resolution of complications. Methods: We identified articles through a reserch in PubMed, Scopus, Web of Science and Ovid MEDLINE for studies published between 1979 and 2019. We included the best available evidence, such as RCTs, non-randomised controlled clinical trials, case–control studies, cohort studies, and case series. About sixty articles were included in this review, four hundred and thirty-six were excluded after reviewing the title or abstract or because they weren't in English. Findings: The possible causes of "difficult" caesarean sections were divided into four categories: difficult access to the lower uterine segment; complicated fetal extraction, laceration or organ damage and abnormal placentation. Conclusions: Knowing in advance the potential technical difﬁculties and resulting risks allows the surgeon to plan appropriate strategies.